Qatar's multi-actors sports strategy: Diplomacy, critics and legitimisation - Søyland, H. S.; Moriconi, M. (International Area Studies Review, 2022)
Drawing on official documents and empirical examples, this article analyses Qatar’s sports strategy to gain attraction and generate soft power globally. The paper shows how the country based has efficiently used sport as a mean for modernisation, diplomacy and soft power, through a strategy based in the participation of national and foreign actors and institutions. While Qatar’s sports diplomacy has been very ambitious, the newfound global attention has led to an increased scrutiny regarding national internal policies. This has resulted in massive criticism regarding corruption allegations and several reports of labour abuses towards the migrant workers in the country. In consequence, critics consider Qatar as an example of sportswashing, which is understood as a deliberate use of sports soft power in seeking to alter a tarnished global reputation. We claim that the Qatari strategy, even having a bit of both, can be used to generate a positive context for social development and we describe how the county has managed to engage foreign actors and institutions to counter external denounces. The context created by successful sports diplomacy strategies and evidence-based external critics might generate an adequate ecosystem to promote substantial cultural and political changes, respect for human rights and individual freedom. In this context, western countries, sport institutions and external actors play (or not) a crucial legitimator role, and so does money.